Survey on mobile and wireless security awareness: user perspectives - Nazri, Nadhirah; Mohamad Ali, Noor Azian; Ibrahim, Jamaludin (International Journal of Science and Research, 2015)
The use of wireless and mobile devices especially smartphones has become the norm nowadays. The emerging and advancement of wireless and mobile devices has brought the issue of security breaches and attacks back into focus. Many users are not aware of the security issues related to wireless and mobile devices. This has resulted in devices becoming attractive targets for malicious attack. In this paper, we discuss and analyze the factors of attack on mobile and wireless platforms and give in-depth overview of the attack mechanism. It is hoped that users will become aware and alert about the security issues and subsequently take the necessary action and precaution to protect themselves.